PENGARUH PAPARAN MEDIA PORNOGRAFI DAN TEMAN SEBAYA TERHADAP PERILAKU SEKS REMAJA KABUPATEN KUDUS - Eny pujiati; dwi septi handayani (Institut Teknologi Kesehatan Cendekia Utama Kudus, 2018)
AbstractTeenagers is a young generation who will be the successor to the struggle of the nation But sometimes a lot of unexpected things that make the quality of teenagers to be shifted in line with the rapid development of science and technology, especially information technology. Given the age of adolescence is a very active age, including active in encouragement and sexual behavior makes it more difficult for teens to make decisions about responsible and healthy sexual behavior. The impact of uncontrolled adolescent sexual behavior is a serious problem for teenagers. According to Green (2003), one's behavior is influenced by three factors, namely predisposing factors, supporting factors, and driving factors. This study aims to determine the effect of exposure to pornographic media and peers against teenage sex behavior Kudus District. This type of research is an explanatory: research using cross sectional approach by way of data collection at one time (point time approachs). The population in this study is high school students in Kudus District using cluster technique that amounted to 2850 people and sampling with simple random sampling with obtained the number of samples of 321 respondents and research instruments using questionnaires. The results showed that all students had contact with pornography, mainly through internet network, as many as 264 respondents (82.2%) were frequently exposed to pornography media and 57 respondents (17.8%) were rarely exposed to pornographic media, peer pressure ( conformity) in the strong category of 234 respondents (72.9%) and weak category 87 respondents (27.1%), conformity in the strong category of 249 respondents (77.6%) and weak category 72 respondents (22.4%) . The result of multivariate analysis showed the influence between exposure of pornography media and adolescent sexual behavior (p = 0,042), the influence of peers (conformity) to adolescent sexual behavior (p = 0,026), and the influence of peers (adaptation) to adolescent sexual behavior (p = p = 0.046). From this research, it is hoped that the school can give intensive information to the students about reproduction health and life skill education as character building, conduct periodic checks on students' mobile phones and meet with parents to discuss matters related to attitude change and the behavior of the students especially the changes in sexual behavior that is being faced by the students.Keywords: Pornographic media exposure, peer influence and teen sex behavior Abstrak Remaja merupakan generasi muda yang akan menjadi penerus perjuangan bangsa Namun terkadang banyak ha-hal tak terduga yang membuat kualitas remaja menjadi bergeser seiring dengan pesatnya arus perkembangan ilmu pengetahuan dan teknologi, terutama teknologi informasi. Mengingat usia remaja adalah usia yang sangat aktif termasuk aktif dalam dorongan dan perilaku seksualnya membuat remaja semakin sulit mengambil keputusan mengenai perilaku seksual yang bertanggung jawab dan sehat. Dampak yang ditimbulkan dari perilaku seksual remaja yang tidak terkontrol merupakan sebuah persoalan serius bagi remaja. Menurut Green (2003), perilaku seseorang dipengaruhi oleh tiga faktor, yaitu faktor predisposisi, faktor pendukung, dan faktor pendorong.Penelitian ini bertujuan untuk mengetahui pengaruh paparan media pornografi dan teman sebaya terhadap perilakuseksremaja Kabupaten Kudus.Jenis penelitian inimerupakan explanatory: research dengan menggunakan pendekatan cross sectional dengan cara pengumpulan data sekaligus pada suatu saat (point time approachs). Populasi dalampenelitian ini adalah siswa sekolah menengah atas yang ada di Kabupaten Kudus dengan menggunakan teknik cluster yang berjumlah 2850orang dan pengambilan sampel dengan simplerandom sampling dengan didapatkan jumlah sampel 321 respondendan instrument penelitiannya dengan menggunakan angket. Hasil penelitian menunjukkan bahwa seluruh siswapernah bersinggungan denganhalyang berkaitan dengan pornografi terutama melalui jaringaninternet, sebanyak 264 responden (82,2%)sering terpapar media pornografi dan57responden (17,8%)jarang terpapar media pornografi, tekanan teman sebaya (konformitas) dalam kategori kuat yaitu234 responden (72,9%) dan kategori lemah87 responden(27,1%), konformitas dalam kategori kuat yaitu 249 responden (77,6%) dan kategori lemah 72 responden (22,4%). Hasilanalisis multivariat menunjukkan adanya pengaruhantara paparan media pornografi dengan perilaku seksualremaja(p = 0,042), adanyapengaruh teman sebaya (konformitas) terhadap perilaku seksualremaja(p = 0,026), dan adanyaperngaruh temansebaya(adaptasi) terhadapperilakuseksualremaja(p=0,046). Dari penelitian ini diharapkan agar sekolah dapat memberikan informasi yang intensif kepada siswanya tentang kesehatan reproduksi dan pendidikan life skill sebagai character building, melakukan pemeriksaansecara berkala terhadap handphone para siswadan melakukan pertemuan dengan orang tua siswa untuk membahas hal-hal yang berkaitandengan perubahansikap dan perilaku para siswaterutamaterhadap perubahanperilaku seksual yangsedang dihadapioleh para siswa.Kata kunci: Paparan media pornografi, pengaruh teman sebaya dan perilaku seks remaja